Pernikahan Akibat Perjodohan di Desa Ketapang Probolinggo Perspektif Utilitarianisme Jeremy Bentham dan Abu Zahrah - Umami, Risa; Nizami, Auliya Ghazna (Department of Comparative Mazhab Comparative, Fakulty of Shariah and Law, 2024)
Abstract: This study explores the phenomenon of arranged marriages in Ketapang Village, Probolinggo, with a focus on the role of parents in determining their children's spouses through arranged marriages. In Islam, a wali (father or grandfather) has the ijbar right to marry off their child, but ideally, this decision should be accompanied by the child's consent to avoid coercion. The study analyzes arranged marriages using the utilitarianism theory of Jeremy Bentham and Abu Zahrah, who each assess actions based on the balance of pleasure and pain, as well as the long-term benefits for individuals and families. The study found several couples who married through arranged marriages, which could harm the parties involved. According to Jeremy Bentham's Utilitarianism, this practice contradicts the principle of happiness. Meanwhile, according to Abu Zahrah, marriage should fulfil the values of justice and benefit. Consequently, the implications of their utilitarian theories support the need for stricter regulations and education to protect individual rights, especially those of women.Keywords: Arranged Marriage, Ijbar Right, Utilitarianism. Abstrak: Penelitian ini mengeksplorasi fenomena perjodohan di Desa Ketapang, Probolinggo, dengan fokus pada peran orang tua dalam menentukan pasangan anak melalui perjodohan. Dalam Islam, seorang wali (ayah atau kakek) memiliki hak ijbar untuk menikahkan anaknya, namun idealnya keputusan ini disertai persetujuan anak untuk menghindari keterpaksaan. Studi ini menganalisis perjodohan menggunakan teori utilitarianisme dari Jeremy Bentham dan Abu Zahrah, yang masing-masing menilai tindakan berdasarkan keseimbangan kesenangan dan rasa sakit serta manfaat jangka panjang bagi individu dan keluarga. Ditemukan terdapat beberapa pasangan yang menikah akibat perjodohan yang dapat merugikan pihak-pihak terkait. Dalam pandangan utilitarianisme Jeremy Bentham praktik perjodohan tersebut bertentangan dengan prinsip kebahagiaan. Sedangkan menurut Abu Zahrah dalam pernikahan harus memenuhi nilai-nilai keadilan dan kemaslahatan. Sehingga dalam impilkasinya, teori utilitarianisme menurut dua tokoh tersebut mendukung perlunya penerapan regulasi yang lebih tegas serta edukasi untuk melindungin hak-hak individu khusunya perempuan. Kata kunci: Perjodohan, Hak Ijbar, Utilitarianisme.